How to cheat at IT project management - Snedaker, Susan (Syngress, 2005)
This book is written with the IT professional in mind. It provides a clear, concise system for managing IT projects, regardless of the size or complexity of the project. It avoids the jargon and complexity of traditional project management (PM) books. Instead, it provides a unique approach to IT project management, combining strategic business concepts (project ROI, strategic alignment, etc.) with the very practical, step-by-step instructions for developing and managing a successful IT project. Its short enough to be easily read and used but long enough to be comprehensive in the right places. * Essential information on how to provide a clear, concise system for managing IT projects, regardless of the size or complexity of the project * As IT jobs are outsourced, there is a growing demand for project managers to manage outsourced IT projects * Companion Web site for the book provides dozens of working templates to help readers manage their own IT projects.
Print version record
Keywords: Information technology -- Management; Project management; Technologie de l'information; Gestion; Gestion de projet; BUSINESS & ECONOMICS; Information Management; BUSINESS & ECONOMICS; Knowledge Capital; Information technology; Management